المحكمة الدستورية في ظل النظام السياسي الجزائري - بن قسمية خالد د.الوافي سعيد -خير الدين مهدي (جامعة المسيلة, 2022)
استحدث المؤسس الدستوري الجزائري المحكمة الدستورية على إثر التعديل الدستوري لسنة 2020، وفي دراستنا لهذا الموضوع وصلنا إلى المكانة الطبيعية و القانونية للمحكمة الدستورية و ما لها من صلاحيات واسعة تمكنها من ضمان احترام الدستور و الحفاظ على استقرار و حماية الدولة و مؤسساتها لتعزيز بناء دولة القانون و هذا مكن الانتقال من أسلوب الرقابة السياسية على دستورية القوانين التي كانت تمارس من طرف المجلس الدستوري إلى أسلوب الرقابة القضائية على دستورية القوانين المعمول به في كثير من الأنظمة الدستورية في العالم، بالاضافة إلى صلاحيتها النظر في الدفع بعدم دستورية النصوص القانونية في الحالات المتعلقة بالنصوص التشريعية و التنظيمية في حال انتهاك الحقوق و الحريات المكفولة من الدستور ورغم كل هذا فان المؤسس الدستوري استطاع الاحتفاظ بجانب من تشكيلة المجلس الدستوري ضمن المحكمة الدستورية الجديدة. The Algerian constitutional founder created the Constitutional Court following the constitutional amendment of 2020, and in our study of this issue we reached the natural and legal status of the Constitutional Court and its wide powers that enable it to ensure respect for the constitution, maintain stability and protect the state and its institutions to enhance the building of the rule of law and This enabled the transition from the method of political control over the constitutionality of laws that were exercised by the Constitutional Council to the method of judicial control over the constitutionality of laws in force in many constitutional systems in the world, in addition to its authority to consider the defense of the unconstitutionality of legal texts in cases related to legislative texts and In the event of a violation of the rights and freedoms guaranteed by the constitution, despite all this, the constitutional founder was able to retain part of the composition of the Constitutional Council within the new Constitutional Court.
Keywords: المحكمة الدستورية، الرقابة الدستورية، التعديل الدستوري